If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 4) + 8x = -14 Reorder the terms: -2(4 + x) + 8x = -14 (4 * -2 + x * -2) + 8x = -14 (-8 + -2x) + 8x = -14 Combine like terms: -2x + 8x = 6x -8 + 6x = -14 Solving -8 + 6x = -14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 6x = -14 + 8 Combine like terms: -8 + 8 = 0 0 + 6x = -14 + 8 6x = -14 + 8 Combine like terms: -14 + 8 = -6 6x = -6 Divide each side by '6'. x = -1 Simplifying x = -1
| 2z-6=10z+6 | | 2=-2(n-7) | | (3(42.5)+x+10)+(42.5+x)=180 | | 6y^2-2y-3=0 | | 5h+9+7h= | | 2(4e)=10 | | 13=3u-14 | | ln(x+3)=0.8 | | 0.666666666667x+6=0.5x+0.25x | | 2(4e)=90 | | 5+.1q=20-.2Q | | (3(42.5)+y+10)+(42.5+y)=180 | | 12+4(z-3)=-3z+6 | | 5w+11=96 | | 2x+2y+1+3x+1=180 | | (A+p)(a^2-ap+p^2)= | | 2(4e)=20 | | 24=4y-16 | | 2x+8+74+5x= | | 2(x+7)+3x=-4 | | 20.6+2.7x=-8.2x | | 15a*2+26a*2+a*2= | | 4x^2-29x=-3x^2-4x-12 | | 0.75=x+1.75 | | (3x+y+10)+(x+y)=180 | | (8y+7)(8y+27)=0 | | 4(3x-2)=6(4x-2) | | 27=5+9(x+8) | | 7+2(b-3)=-9 | | 2x^2-6x-8=8 | | x(5x+3)=2x^2-5x+3 | | 62-x=281 |